Experimental use of a novel single-port gasless laparoendoscopic operative field formation device. (January 2017) - Hu, Hai; Zhang, Kai; Zhao, Gang; Jiang, Zhaoyan; Huang, Anhua; Cai, Jingli; Xu, Anan; Li, Haidong; He, Chuanqi; Ding, Kan; Lu, Ruiqi; Ye, Ruiqi
Abstract: Introduction: Traditional laparaendoscopic surgery using CO2 pneumoperitoneum is associated with complications and the existing gasless laparaendoscopic surgery has shortcomings such as poor visibility in the operation field. To overcome the disadvantages of the current lifting gasless laparaendoscopic operation platforms, we developed an inflatable device for gasless laparoscopic operation field formation (LOFF) that can be internally installed and applied in practice. Methods: We initially designed operation platforms for gasless laparaendoscopic single-port (GLESP) surgery. Subsequently, a triangular prismatic LOFF device was selected and applied successfully to GLESP cholecystectomy of five pigs. Ultimately, using pigs as a model, three surgical approaches (LOFF-assisted laparaendoscopic single-site (LOFF-LESS), LESS surgery, and traditional lifting (GLESP) were compared, and the advantages and drawbacks of inflatable devices for gasless laparoscopic operation field assessed. Results: The use of the LOFF device in GLESP cholecystectomy was first evaluated. The time for surgical space formation (4.4 ± 1.2 and 4.8 ± 1.0), the operating time for gallbladder removal (25.2 ± 4.8 and 25.4 ± 2.7), and the loss of blood (9.4 ± 3.1and 9.2 ± 2.4) was similar between LESS and LOFF, respectively (Table 2). In contrast these parameters were higher in GLESP (6.6 ± 1.0, 30.3 ± 4.4 and 10.1 ± 2.0, respectively. The LOFF-LESS surgery exhibited a clearer exposure of the surgical field and shorter operating time than the GLESP surgery. LESS technology showed less postoperation pain, fast recovery, and extremely high cosmetic satisfaction. Conclusion: The LOFF device provides a safe, effective, and feasible operation platform that can be internally installed and inflated for GLESP surgery during cholescytectomy in animal models. Highlights: Traditional carbon dioxide laparaendoscopy is a high risk surgery. The existing gasless laparaendoscopies have attendant poor visibility of the abdominal cavity. We developed an inflatable device for gasless laparoscopic operation field formation (LOFF).